Comparison Of Epidural Analgesia Vs Intraoperative Peri-Articular Injection For Pain Management Following Total Knee Arthroplasty - Rahman Rasool Akhtar; Riaz Ahmed; Waqas Ali; Hira Waris (Journal of Rawalpindi Medical College)
Objective: To compare epidural analgesia vs intraoperative peri-articular injection for pain management following Total Knee Arthroplasty.